Active learning strategies in higher education - Misseyanni, Anastasia; Papadopoulou, Paraskevi, 1961-; Marouli, Christina, 1961-; Lytras, Miltiadis D., 1973- (Emerald Publishing Limited, 2018)
In the era of the 21st century knowledge society, higher education can play an important role as a driver for innovation, leadership, and creativity, as it helps develop not only well informed and knowledgeable citizens but also responsible and creative individuals. The challenges of globalization, tightly linked with rapid developments in Information and Communication Technologies (ICT) and the need to address issues of quality and inclusiveness for a better quality of life and a sustainable future, have become drivers of change in higher education institutions. We are experiencing a shift towards more interdisciplinary curricula and a more integrated and student-centered approach to teaching. Instructors increasingly use active learning and other pedagogies of engagement as a means to increase learning and improve student attitudes. This book explores best practices for effective active learning in higher education. Experienced instructors from different disciplines and countries share their experiences and reflect on best practices, as well as on the theoretical underpinnings of active learning. Contributors share their thinking on strategies based on different active learning methods such as the use of ICTs, collaborative learning and experiential learning, as well as their implications for teaching, assessment, curriculum design and higher education administration. Active learning provides skills for real life problem solving and prepares students to become responsible and active citizens. This book will be a very significant resource for educators who are interested in making a difference in students' lives.